Professores iniciantes de Geografia: processos de recontextualização da formação inicial no contexto da prática pedagógica - Rosa, Claudia do Carmo (2017)
Even considering the strong influence of the school as a regulatory framework in the pedagogical discourse of the beginning teacher of Geography, initial formation is a constitutive dimension in the processes of recontextualization of pedagogical practice. For this thesis, a research was developed directly focused on the formation and teaching performance carried out by the beginner teachers of Geography of the Metropolitan Region of Goiânia and of Anápolis. The objectives of this research are: 1) to understand how the pedagogical practice of beginning teachers of Geography occurs, having as reference their initial formation and the processes of recontextualization in the classroom; 2) to analyze the insertion of the Geography teacher in the professional activity; how the beginning teacher of Geography takes its first steps in the teaching profession; 3) from the processes of recontextualization, to identify that Geography is constructed and (re) produced in the school practice of the beginning teachers in the first years of teaching career; 4) to reflect on the main theoretical bases of Geography that present themselves in the context of the pedagogical practice of teachers at the beginning of their careers; 5) to know the didactic-pedagogical foundations of School Geography that are manifested in the context of the pedagogical practice and the pedagogical discourse of the beginning teachers, and, finally, 6) to analyze the conflicts of the teaching profession, highlighting the difficulties, the wishes and the possible overcomes facing the demands of being a professor of Geography. This research has a qualitative nature and is based on dialectics as a basic principle for the analysis and interpretation of the results. Data collection was done through the use of three research instruments: online questionnaire, open interview and observation of classes. The online questionnaire was requested from Geography teachers who work in the educational networks of the RMG and of Anápolis as an exploratory dimension of the research research. The open interview and the observation of classes were carried out specifically with teachers qualified in Geography who are practicing the profession of Geography teacher in Basic Education, with a minimum of one year and maximum of seven years of teaching. As a theoretical and methodological reference, the contributions of national and international authors in the area of Education and in particular of Geography, which base the discussions on teacher training and performance, teaching Geography and School Geography, are on the one hand. On the other hand, Bernstein's theoretical support especially his productions about the pedagogical discourse model, which articulates concepts such as recontextualization, vertical discourses and horizontal discourses. The data revealed that even considering the intervention and / or influence of different regulatory frameworks (teaching system, curriculum, school context, textbook) in the pedagogical practice of beginning teachers, the initial training is dimension to teach Geography. When teachers consider the students' previous knowledge as a result of their daily practices, the student is an active subject in the teachinglearning process, working with the geographic contents in the promotion of meaningful learning, working with the geographic concepts, the subjects dealt with on a local / global geographic scale, among others. And to those who deny the initial formation, it is believed that there are dimensions of geographic science even if unconsciously in the pedagogical practice of the beginning teacher of Geography, for example, when they problematize and seek to contextualize with the immediate reality of the students. However, there are challenging dimensions to being a teacher early in your career.